Market Incompleteness and Divergences Between Forward and Futures Interest Rates - Kane, Edward J. (Journal of Finance, 1980)
Edward J. Kane, Market Incompleteness and Divergences Between Forward and Futures Interest Rates, The Journal of Finance, Vol. 35, No. 2, Papers and Proceedings Thirty-Eighth Annual Meeting American Finance Association, Atlanta, Georgia, December 28-30, 1979 (May, 1980), pp. 221-234